Inhibitory mechanism of quercetin on Alicyclobacillus acidoterrestris - Liang, Xinhong; Tu, Cunjian; Li, Yongchao; Sun, Junliang; Zhao, Ruixiang; Ran, Junjian; Jiao, Lingxia; Huang, Junchao; Li, Junrui (Frontiers in Microbiology, 2023)
In this the antibacterial of quercetin against Alicyclobacillus acidoterrestris was evaluated by measuring the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). Subsequently, the effect of quercetin on Alicyclobacillus acidoterrestris cell membrane was evaluated through scanning electron microscopy (SEM), surface hydrophobicity determination, diacetate fluorescein staining and propidium iodide (PI) staining. Additionally, the effects of quercetin on intracellular macromolecules and cell metabolism were explored by measuring the culture medium protein, bacterial protein and intracellular sodium and potassium adenosine triphosphate (ATP) enzyme activity. The results revealed that quercetin exhibited the MIC and MBC values of 100 ug/mL and 400 ug/mL, respectively, against Alicyclobacillus acidoterrestris. The SEM results revealed that quercetin could induce irreversible damage to the cell membrane effectively.Moreover, quercetin could enhance the surface hydrophobicity of Alicyclobacillus acidoterrestris.The results of flow cytometry and fluorescence microscopy analyses revealed that quercetin could promote cell damage by altering the cell membrane permeability of Alicyclobacillus acidoterrestris, inducing the release of nucleic acid substances from the cells. Furthermore, the determination of protein content in the culture medium, bacterial protein content, and the Na(+)/K(+)-ATPase activity demonstrated that quercetin could reduce the intracellular protein content and impedes protein expression and ATPase synthesis effectively, leading to apoptosis.